Optimal dosing of enoxaparin in overweight and obese children. Issue 12 (27th July 2022) - Derbalah, Abdallah; Duffull, Stephen; Sherwin, Catherine M.; Job, Kathleen; Al‐Sallami, Hesham
Abstract : Aim: Current enoxaparin dosing guidelines in children are based on total body weight. This is potentially inappropriate in obese children as it may overestimate the drug clearance. Current evidence suggests that obese children may require lower initial doses of enoxaparin, therefore the aim of this work was to characterise the pharmacokinetics of enoxaparin in obese children and to propose a more appropriate dosing regimen. Methods: Data from 196 unique encounters of 160 children who received enoxaparin treatment doses were analysed. Enoxaparin concentration was quantified using the chromogenic anti factor Xa (anti‐Xa) assay. Patients provided a total of 552 anti‐Xa samples. Existing published pharmacokinetic (PK) models were fitted and evaluated against our dataset using prediction‐corrected visual predictive check plots (pcVPCs). A PK model was fitted using a nonlinear mixed‐effects modelling approach. The fitted model was used to evaluate the current standard dosing and identify an optimal dosing regimen for obese children. Results: Published models of enoxaparin pharmacokinetics in children did not capture the pharmacokinetics of enoxaparin in obese children as shown by pcVPCs. A one‐compartment model with linear elimination best described the pharmacokinetics of enoxaparin. Allometrically scaled fat‐free mass with an estimated exponent of 0.712 (CI 0.66‐0.76) was the most influential covariate on clearance while linear fat‐free mass was selected as the covariate on volume. Simulations from the model showed that fat‐free mass‐based dosing could achieve the target anti‐Xa activity at steady state in 77.5% and 78.2% of obese and normal‐weight children, respectively, compared to 65.2% and 75.5% for standard total body weight‐based dosing. Conclusions: A population PK model that describes the time course of anti‐Xa activity of enoxaparin was developed in a paediatric population. Based on this model, a unified dosing regimen was proposed that will potentially improve the success rate of target attainment in overweight/obese patients without the need for patient body size categorisation. Therefore, prospective validation of the proposed approach is warranted.